A Muted Fury : Populists, Progressives, and Labor Unions Confront the Courts, 1890-1937 - Ross, William G. (Book collections on Project MUSE., 2014)
For half a century before 1937, populists, progressives, and labor leaders complained bitterly that a ""judicial oligarchy"" impeded social and economic reform by imposing crippling restraints on trade unions and nullifying legislation that regulated business corporations. A Muted Fury, the first study of this neglected chapter in American political and legal history, explains the origins of hostility toward the courts during the Progressive Era, examines in detail the many measures that antagonists of the judiciary proposed for the curtailment of judicial power, and evaluates the su.